Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I found this question somewhere and have been unable to solve it. It is a modification of a very common algebra question.

$\text{Let }y=\sqrt{5+\sqrt{5-\sqrt{5+\sqrt{5-...}}}} $, what is the nearest value of $y^2 - y$?

$\textbf {(1) } 1 \qquad \textbf {(2) } \sqrt5 \qquad \textbf {(3) } 4 \qquad \textbf {(4) } 2\sqrt5$

I worked the problem and got $$y^2 - y = 5+ \sqrt{5-\sqrt{5+\sqrt{5-...}}} -\sqrt{5+\sqrt{5-\sqrt{5+\sqrt{5-...}}}} \\ = 5+ \sqrt{5-y} - y = 5-y + \sqrt{5-y}$$ What do I do next?

share|cite|improve this question
5  
the $\infty$ is unnecessary. – ILoveMath Dec 1 '13 at 18:36
1  
The $\infty$ even looks wrong. – heinrich5991 Dec 1 '13 at 22:21
up vote 14 down vote accepted

Let's let

$$y=\sqrt{5+\sqrt{5-{\sqrt{5+{\sqrt5-\cdots}}}}}$$

and

$$z=\sqrt{5-\sqrt{5+{\sqrt{5-{\sqrt5+\cdots}}}}}$$

and assume that both limits exist. Note that

$$y^2=5+z\quad\text{and}\quad z^2=5-y$$

Hence

$$\begin{align} y^2-y&=(5+z)-y\\ &=5-(y-z)\\ &=5-{y^2-z^2\over y+z}\\ &=5-{(5+z)-(5-y)\over y+z}\\ &=5-{z+y\over y+z}\\ &=4 \end{align}$$

Added 5/6/14: I thought I'd go ahead and add a proof that the two limits actually do exist. I'm not sure this is the simplest proof -- I'll be happy to see something slicker -- but here goes.

Define the sequence of $y_n$'s by $y_n=\sqrt{5+\sqrt{5-y_{n-1}}}$ with $y_1=\sqrt{5+\sqrt{5}}$, and let $z_n=\sqrt{5-y_n}$. It's easy to show (by induction) that $2\lt y_n\lt4$ for all $n$, so it suffices to show that the sequence of $y_n$'s has a limit.

I'll do so by showing that it's a Cauchy sequence, and I'll do that by showing that $\sum|y_n-y_{n-1}|$ converges.

We have $y_n^2-5=\sqrt{5-y_{n-1}}$, hence

$$y_n^2-y_{n-1}^2=\sqrt{5-y_{n-1}}-\sqrt{5-y_{n-2}}={y_{n-2}-y_{n-1}\over\sqrt{5-y_{n-1}}+\sqrt{5-y_{n-2}}}$$

hence

$$|y_n-y_{n-1}|={|y_{n-2}-y_{n-1}|\over|y_n+y_{n-1}|\left(\sqrt{5-y_{n-1}}+\sqrt{5-y_{n-2}}\right)}\lt{|y_{n-1}-y_{n-2}|\over|2+2|(1+1)}={1\over8}|y_{n-1}-y_{n-2}|$$

where we've used the inequalities $2\lt y_n\lt 4$ (for all $n$) in the denominator. It follows that $\sum|y_n-y_{n-1}|$ is bounded by a geometric series with ratio $1/8$, hence converges.

Added 6/29/16: For a nice example of what can go wrong if you assume a limit exists but don't bother to check if it actually does, see this problem.

share|cite|improve this answer

You were on the right track. Put

$$x=\sqrt{5+\sqrt{5-\sqrt{5+\ldots}}}\implies x^2=5+\sqrt{5-\sqrt{5+\ldots}}\implies$$

$$x^4-10x^2+25=5-\sqrt{5+\sqrt{5-\ldots}}\implies$$

$$x^4-10x^2+20=-\sqrt{5+\sqrt{5-\ldots}}=-x\implies\;\ldots\ldots$$

share|cite|improve this answer
    
,I think the sign '+,-' toggles. – lab bhattacharjee Dec 1 '13 at 18:36
    
Indeed. Editing on its way and thanks. – DonAntonio Dec 1 '13 at 18:36
    
what is the answer? The approximation should come around 4. – shaurya gupta Dec 7 '13 at 16:43

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.